143k views
5 votes
Solve the system using elimination. 3x – y = 28 3x + y = 14 (8, –4) (–4, 8) (–7, 7) (7, –7)

User Yassin
by
5.9k points

1 Answer

4 votes

Answer:

x=7, y=-7

Explanation:

3x – y = 28

3x + y = 14

Add the two equations together

3x – y = 28

3x + y = 14

---------------------

6x = 42

Divide by 6

6x/6 = 42/6

x = 7

3x – y = 28

3x + y = 14

Multiply the second equation by -1, then add

3x – y = 28

-3x - y = -14

-------------------

-2y=14

Divide by -2

-2y/-2 = 14/-2

y = -7

User ZioBudda
by
6.0k points